Ein Beitrag zur asymptotischen Analyse der hydraulischen Ventilsteuerungen - Schröders, Simon (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2022)
A method based on the singular perturbation theory and the averaging method is developed for the dynamic analysis of hydraulic valves. Periodic solutions are calculated and stability is analyzed under the influence of non-smooth phenomena. Based on this analysis, reduced models are developed, which exhibit significantly improved computational time efficiency, both in the simulation of non-stationary motions as well as in nonlinear valve control.